Energy Harvesting and Propulsion of Pitching Airfoils with Passive Heave and Deformation. - Fernández-Feria, Ramón; Alaminos-Quesada, Javier (AIAA, 2021)
A general formulation for the fluid–structure interaction of an airfoil undergoing prescribed pitching and passive heave and deformation about an arbitrary axis is given in the linearized potential flow limit. The resulting three algebraic equations provide the heave and deformation amplitudes linearly from two of the equations, as well as the torque that generates the pitching motion (and hence the input power) from the third. Both, the energy harvesting and the propulsion problems are analyzed. In the first case, energy is harvested at the pivot point through dampers so that the efficiency is obtained once the heaving motion and the input power are computed. In the second problem, the prescribed pitch and the computed heave and deformation yield the thrust as well as the propulsive efficiency with the obtained input power. The present analytical results allow for a general survey of these two physical problems as the multiple governing parameters are varied. It is generally found that the best performance is achieved around the first natural frequency, which is obtained here from a simple algebraic expression. The formulation is validated with previous experimental and numerical results. The effect of flexibility maximizing the energy harvesting efficiency is particularly analyzed.
https://openpolicyfinder.jisc.ac.uk/id/publication/9876
Keywords: Recursos energéticos renovables; Aerodinámica; Extracción de energia renovable; Propulsión